Political elites and the new Russia : the power basis of Yeltsin's and Putin's regimes - Steen, Anton, 1949- (BASEES/RoutledgeCurzon series on Russian and East European studies, 2003)
An analysis of the role of elites under Yeltsin and Putin, dicussing how far they form a coherent political culture, and if this culture has been in step with, or at odds with, the reform policies of the Kremlin leadership.